PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR SISWA MELALUI PENERAPAN METODE PEMBELAJARAN PROBLEM SOLVING PADA PELAJARAN KELISTRIKAN OTOMOTIF KELAS XI SMK NEGERI 5 SURAKARTA - Firdzaus K, Muhammad (Jurnal Nosel, 2013)
The purpose of this research improves activeness and learning outcomes of student XI TO B class on learning theory at automotive electrical lesson SMK Negeri 5 Surakarta for academic year 2012/2013. This data the research were activeness and learning outcomes of student. The Collecting of the data by using four ways, there was interview, observation, test, and questionaire. The observation sheet use six indicators of activeness : asking, argue, listening, reading, writing, and discussion. The data of the research was analyzed with descriptive analyse techniques. The research includes action research in education, namely classroom action research (PTK). This research was by one meeting activities before the cycle. PTK was carried out with two cycle?s, each cycle two meeting?s with one test in last of second meeting. Based on the result, result of research  was concluded that application of Problem Solving Learning  Method improved 9,25% activeness of  student XI TO B class on learning  theory   at  automotive   electrical   lesson SMK  Negeri  5  Surakarta  for academic year 2012/ 2013. Beside that application of Problem Solving Learning Method improved learning outcome of student XI TO B class on learning theory at automotive electrical lesson SMK Negeri 5 Surakarta for academic year 2012/2013.